ANALYSIS OF THE ROLE AND POTENTIAL OF THE PENTAHELIX IN EFFORTS TO PREVENT DIVORCE - Ahmad Jalaluddin Faisol; Ainol Yaqin; Muhammad Taufiq (Universitas Nurul Jadid, 2026)
This study examines the role and potential of the pentahelix model in preventing divorce in Pamekasan, as well as the forms of assistance provided by the Ministry of Religious Affairs in fostering keluarga sakinah. The research employs an empirical legal approach with a qualitative case study design. Data were collected through in-depth interviews, observations, and document analysis involving key stakeholders, including government institutions, academics, community leaders, media, and the private sector. The findings reveal that divorce prevention efforts are dominated by government and community actors, particularly through premarital guidance, counseling, and mediation conducted by the Ministry of Religious Affairs and KUA. Meanwhile, the roles of academia, media, and the private sector remain limited and not yet fully integrated. The Ministry of Religious Affairs implements both preventive and curative programs, such as Bimbingan Perkawinan (Bimwin), family counseling, religious outreach, and sakinah family development. These efforts have contributed to improving legal and religious awareness and enhancing family resilience. However, the effectiveness of these programs remains suboptimal, as indicated by fluctuating divorce rates. This study concludes that the lack of synergy among pentahelix actors is the main challenge in divorce prevention. Strengthening collaborative and integrative approaches is essential to enhance the effectiveness of family resilience programs.